Getting to grips with clinical governance - Harrison, Simon; Pollock, Colin; Symons, Stephanie (Tfm Pub., 2003)
The authors of this book have approached the topic from diverse backgrounds: urological surgery, general practice, and public health medicine. The result is a commentary on the evolution of clinical governance that has the firm anchors of practicality and realism. It looks at clinical governance from the perspective of the practicing clinician and explains what clinical governance has to offer them.